Principles of land ownership and their application in the Malaysian Land Law and Islam - Mohamad, Nor Asiah; Sallahudin, Suhaila; Abdul Samad, Abdullah Syamil; Razak, Anith Najhan; Muhafif, Munyra; Musiman, Norsyahirah (USIM, 2019)
This article explains and discuss the application of the Malaysian land principles under the Malaysian Torrens system with the land system in Islam